Gender inequalities in ownership and control of land in Africa: Myths versus reality - Doss, Cheryl; Kovarik, Chiara; Peterman, Amber; Quisumbing, Agnes R.; van den Bold, Mara (International Food Policy Research Institute, 2013)
The objective of this paper is to explore, conceptually and empirically, the levels and relative inequalities in landownership between women and men in African countries. The first section of the paper engages in a conceptual discussion of how to measure gendered land outcomes, what ownership and control mean in different contexts, and why attention to these factors is important for the development of gender and land statistics. The second section of the paper systematically reviews existing evidence from microlevel large sample studies by region to summarize recent trends in land access, ownership, and control by sex. The third section presents new statistics from a variety of nationally representative and large-scale unpublished data on gender and land in Africa. Results provide not only a nuanced understanding of the importance of measuring land indicators for gendered development in Africa and globally but also new statistics on a variety of land outcomes to aid stakeholders in the discussion of gender-land inequalities.